2019
DOI: 10.1002/clc.23223
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between aortic dissection and atrial fibrillation: Findings from a huge national database

Abstract: Objective To explore the link between aortic dissection (AD) and atrial fibrillation (AF). Methods Using the National Health Insurance Research Database (NHIRD), cohorts were constructed for evaluating the incidence of AF in patients with AD (study 1) and the incident AD among AF patients (study 2) based on propensity matching analysis. Cox proportion hazard regression models were used to examine the effect of AD on the risk of AF, shown as hazard ratios (HRs) with 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The incidence of AF in AAD patients is reported to be approximately 12%-17%. [1][2][3] In this study, AF was observed in 27/139 patients (19%), similar to the findings of previous studies. A study based on a Taiwanese national database reported that patients with AF had a 1.18-fold higher incidence of AAD than those without AF.…”
Section: Prognostic Impact Of Af For Aadsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of AF in AAD patients is reported to be approximately 12%-17%. [1][2][3] In this study, AF was observed in 27/139 patients (19%), similar to the findings of previous studies. A study based on a Taiwanese national database reported that patients with AF had a 1.18-fold higher incidence of AAD than those without AF.…”
Section: Prognostic Impact Of Af For Aadsupporting
confidence: 92%
“…Acute aortic dissection (AAD) is often complicated by atrial fibrillation (AF), with an incidence of 12%-17%. [1][2][3] These conditions share common risk factors, including atherosclerosis, hypertension, sleep apnea, and advanced age. [4][5][6][7][8][9][10] However, research on whether the presence of AF contributes to a worse prognosis in patients with AAD is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Von Kodolitsch et al showed that anticoagulation with warfarin is feasible even in post-surgical patients with type A aortic dissection as it did not affect aortic growth and was not associated with late mortality nor with late aortic events, thus suggesting that patients requiring anticoagulation due to other indications should be indeed considered on individualized basis to receive such treatment [16]. This holds true especially for atrial fibrillation, which is not uncommon among patients with aortic dissection [17]; few reports have addressed the issue of anticoagulation in this scenario with heterogeneous results and patient-tailored therapy seems the best treatment option until larger studies will focus on this topic [18,19].…”
Section: Discussionmentioning
confidence: 99%
“… 23 Our analysis showed that chronic kidney disease was associated with 3.2‐fold increased odds of AD occurrence in women and 2.4‐fold increased odds of occurrence in men. Similarly, there have been few studies linking atrial fibrillation to AD, 24 although evidence has shown a high prevalence of atrial fibrillation in patients with AD (16.1% in men and 14.3% in women in the OxVasc [Oxford Vascular Study]). 2 We found that the elevated odds of AD occurrence associated with atrial fibrillation were 58% stronger in women than in men.…”
Section: Discussionmentioning
confidence: 99%